Reaction of SiCl2·dipp with K[Ge9{Si(SiMe3)3}3] – Synthesis and Characterization of [K(dipp)2][Ge9{Si(SiMe3)3}3]·tol and [dipp‐H][Ge9{Si(SiMe3)3}3]·2acn [dipp = 1, 3‐Bis(2, 6‐Diisopropylphenyl)imidazol‐2‐ylidene]. Issue 22 (28th October 2016) - Fischer, Christina; Klein, Wilhelm; Jantke, Laura‐Alice; Schiegerl, Lorenz J.; Fässler, Thomas F.
Abstract : From solutions of K[Ge9 {Si(SiMe3 )3 }3 ] with 1, 3‐bis(2, 6‐diisopropylphenyl‐)imidazol‐2‐ylidene (dipp) two new compounds were obtained. From toluene, single crystals of [K(dipp)2 ][Ge9 {Si(SiMe3 )3 }3 ]· tol (1 ) (tol = toluene) were isolated and the crystal structure was determined [monoclinic, P 21 / c, a = 16.8386(3), b = 24.6597(5), c = 30.2988(6) Å, β = 101.813(2)°, V = 12314.7(4) Å 3, Z = 4, 24192 independent reflections, R 1 = 0.046, wR 2 = 0.084]. The investigation of single crystals from acetonitrile solution revealed the formation of [dipp‐H][Ge9 {Si(SiMe3 )3 }3 ]· 2 acn (2 ) (acn = acetonitrile) [orthorhombic, P 21 21 21, a = 13.4484(4), b = 25.8775(7), c = 26.4390(9) Å, V = 9201.1(5) Å 3, Z = 4, 18065 independent reflections, R 1 = 0.031, wR 2 = 0.052]. The two [Ge9 {Si(SiMe3 )3 }3 ] – entities show the minimal and maximal distortion of the central tricapped prism that have been reported to date. All compounds were characterized by ESI‐MS, NMR and Raman spectroscopy, and DFT calculations. Abstract :